Undernutrition, vitamin A and iron deficiency are associated with impaired intestinal mucosal permeability in young Bangladeshi children assessed by lactulose/mannitol test - Hossain, Md Iqbal; Haque, Rashidul; Mondal, Dinesh; Mahfuz, Mustafa; Ahmed, Am Shamsir; Islam, Mohammad Munirul; Guerrant, Richard Littleton; Petri, William Arthur; Ahmed, Tahmeed J. (© 2017 Public Library of Science, 2018)
This article was published in the PLoS ONE [© 2016 Public Library of Science] and the definitive version is available at: http://doi.org/10.1371/journal.pone.0164447 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0164447